EPILEPSY AND MIGRAINE: NEUROIMAGING AND NEUROPATHOPHYSIOLOGICAL PARALLELS - V. V. Evstigneev; A. N. Michailov; O. V. Kistsen; K. A. Sadokcha; R. A. Sakovich (Эпилепсия и пароксизмальные состояния, 2016)
The aim of this work was to elucidate the structural-metabolic and neuropathophysiological features of epilepsy and migraine, as these diseases share common pathogenetic mechanisms.Materials and methods. Seventy patients with migraine and fifty-six with epilepsy conducted a study using diffusion tensor MRI. Proton spectroscopy performed on 28 patients with epilepsy and 22 with migraine.Results. Data were obtained, indicating changes in fractional anisotropy and average diffusion coefficient and concentration of the main neurometabolites for epilepsy and migraine that characterize the commonality of the pathogenesis of these diseases.Conclusion. The research results allowed to establish the leading role of the hippocampus in the realization paroxysmal states and their pathophysiological basis of the comorbidity.